Computational modelling of panchromatic porphyrins with strong NIR absorptions for solar energy capture - Agnihotri N. (My University, 2025)
Five potential push-pull porphyrin dyes (PR1-PR5) substituted with extended rylene anhydride units (n = 1–5) as electron acceptors and (4-dimethylamino) phenyl ethynylene as an electron donor have been investigated computationally using density functional theory and time dependent-density functional theory. Their molecular orbital energies are reported together with their singlet and triplet electronic transition energies, oscillator strengths and charge transfer characteristics. These sensitizers are panchromatic, their fully-allowed charge transfer transitions extend well into the near infrared and their HOMO and LUMO energies appear well-matched to the band gap and electrochemical potential requirements of dye-sensitized solar cells (DSSCs). © 2016 Elsevier B.V.